Usefulness of serial lung ultrasound for a severe COVID-19 patient on extracorporeal membrane oxygenation. (2021) - Taniguchi, Hayato; Ohta, Souichi; Honzawa, Hiroshi; Takahashi, Kouhei; Iwashita, Masayuki; Abe, Takeru; Takeuchi, Ichiro
Abstract: Computed tomography (CT) is the most reliable method to evaluate the progression of COVID-19 pneumonitis. However, in a pandemic, transportation of critically ill invasively ventilated patients to radiology facilities is challenging, especially for those on extracorporeal membrane oxygenation (ECMO). Notably, lung ultrasound (LUS) is a favored alternative imaging modality due to its ease of use at the point of care, which reduces the infectious risk of exposure and transmission; repeatability; absence of radiation exposure; and low cost. We demonstrated that serial LUS compares favorably with other imaging modalities in terms of usefulness for evaluating lung aeration and recovery in an ECMO-managed COVID-19 patient. Highlights: Serial lung ultrasound (LUS) correlates with computed tomography findings and can evaluate COVID-19 more specifically than laboratory findings. LUS may be useful for the detection of P-SILI.